Analisis Urea-Kreatinin Tikus Putih pasca Pemberian Ekstrak Buah Mahkota Dewa dan Herba Pegagan - WAHONO SUMARYONO; AGUNG ERU WIBOWO; SRI NINGSIH; KURNIA AGUSTINI; ROS SUMARNY; FITRIANIAR AMRI; HENDIG WINARNO (Fakultas Farmasi Universitas Pancasila, 2008)
The evaluation of toxicity of a mixed herbal extract containing mahkota dewa fruits (Phaleria macrocarpa Scheff. Boerl) and pegagan leaves (Centella asiatica L. Urban) on Wistar-strain rats had been carried out by the determination of the urea and creatinine content in urine and plasma after feeding. Oral doses of 100 mg, 500 mg, and 2500 mg of the mixed extract/kg body Weight were administered for 16 consecutive weeks to three groups of rats. Each treated group consisted of 15 males and 15 females, and the control group was represented by 10 males and 10 females. Samples of urine and plasma of the treated groups were taken at the time right before treatment (Week zero) and at Sm, 16th, 18th Week, while those of the control were taken at zero Week, 8th, and 16th Week, respectively. The result showed that theurea and creatinine contents among the treated and control groups were not signihcantly different. It could be concluded that oral administration ofthe mixed extract by a dose up to 2500 mg/kg body weight for 16 Weeks did not influence the urea and creatinine contents both in urine and plasma of the treated animals. Based on this result, it could be assumed that the use of the mixed extract is safe.